2009
DOI: 10.3324/haematol.2008.003129
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 regulatory T cells are associated with persistent split erythroid/lymphoid chimerism after allogeneic hematopoietic stem cell transplantation for thalassemia

Abstract: BackgroundThalassemia major can be cured with allogeneic hematopoietic stem cell transplantation. Persistent mixed chimerism develops in around 10% of transplanted thalassemic patients, but the biological mechanisms underlying this phenomenon are poorly understood. Design and MethodsThe presence of interleukin-10-producing T cells in the peripheral blood of eight patients with persistent mixed chimerism and five with full donor chimerism was investigated. A detailed characterization was then performed, by T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 56 publications
5
68
2
Order By: Relevance
“…21 Similar results were obtained by Felfly and Trudel in thalassemic mutant mice which were transplanted in order to determine the minimal percentage of normal bone marrow cells necessary to correct the thalassemic phenotype in a competitive re-population transplantation assay. 27 They found a 2-to 2.5-fold amplification of normal RBC compared to white blood cells in the peripheral blood of mice with 19-24% bone marrow chimerism, indicating an in vivo selective advantage for the normal RBC.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…21 Similar results were obtained by Felfly and Trudel in thalassemic mutant mice which were transplanted in order to determine the minimal percentage of normal bone marrow cells necessary to correct the thalassemic phenotype in a competitive re-population transplantation assay. 27 They found a 2-to 2.5-fold amplification of normal RBC compared to white blood cells in the peripheral blood of mice with 19-24% bone marrow chimerism, indicating an in vivo selective advantage for the normal RBC.…”
Section: Discussionmentioning
confidence: 52%
“…The potential role of T regulatory cells in establishing persistent mixed chimerism has been recently pointed out. [21][22][23][24] However, independently of the biological mechanisms involved, data from several studies have shown that patients with persistent mixed chimerism have clinical control of the disease, despite the presence of an extremely low proportion of donor nucleated cells. [10][11][12][13]25 The majority of studies concerning the assessment of persistent mixed chimerism have, however, almost exclusively focused attention on the percentage of donor engraftment in the nucleated cells rather than in the mature erythrocytes, cells functionally crucial for patients affected by hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Therefore graft rejection probabilities were higher in patients with MC detected within the first months after the transplant and proportional to the amount 1 regulatory cells are associated with PMC and may play an important role in sustaining long-term tolerance in vivo. 11 Up to now, it is not clear if the mechanisms inducing an immunological tolerance in patients with PMC might also influence a different maturation of the donor erythroid precursors after HSCT for hemoglobinopathies. However, the presence of a split chimerism between mature erythrocytes and their progenitors has been recently described in persistent mixed chimera patients 13,14 with a predominant erythroid engraftment in the peripheral blood, while the proportion of erythroid precursors (BFU-E-burst forming unit erythroid) colonies and nucleated cells of donor origin in the bone marrow were equivalent (Fig.…”
Section: -3mentioning
confidence: 99%
“…A possible explanation could be the presence of high proportions of IL-10-producing type 1 regulatory cells (Tr1) in such patients, possibly as a result of MC providing chronic allogenic stimulus. 7 Endogenous IL-10 inhibits alloreactivity against both host and donor cells and may be responsible for the induction and maintenance of long-term tolerance. Such patients are reported to have a lower incidence of GVHD.…”
mentioning
confidence: 99%